Towards multi-fidelity simulation of flows around an underwater vehicle with appendages and propeller. Issue 1 (January 2022) - Zhou, Zhideng; Li, Zhaobin; He, Guowei; Yang, Xiaolei
Highlights: Propose to simulate the flow around an underwater vehicle in a multifidelity way. The hull is geometrically resolved using the immersed boundary method. The propeller is parameterized using the actuator disk model. The proposed method is applied to the flow over DARPA suboff. Abstract: Flow around a real-life underwater vehicle often happens at a high Reynolds number with flow structures at different scales from the boundary layer around a blade to that around the hull. This poses a great challenge for large-eddy simulation of an underwater vehicle aiming at resolving all relevant flow scales. In this work, we propose to model the hull with appendages using the immersed boundary method, and model the propeller using the actuator disk model without resolving the geometry of the blade. The proposed method is then applied to simulate the flow around Defense Advanced Research Projects Agency (DARPA) suboff. An overall acceptable agreement is obtained for the pressure and friction coefficients. Complex flow features are observed in the near wake of suboff. In the far wake, the core region is featured by a jet because of the actuator disk, surrounded by an annular region with velocity deficit due to the body of suboff.